2018
DOI: 10.15695/jstem/v1i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Taking a Look at the Heath Sciences and Technology Academy (HSTA):Student-Research Partnership Increases Survey Size, Hands-on STEM Learning, and Research-Community Connections

Abstract: This paper explores the dynamics of a research partnership between a practicing clinician/research and 34 West Virginia high school students participating in a precollege STEM intervention program. The collaboration provided a more diverse study sample to the clinician for examining attitudes about knee osteoarthritis in adults over 40. It provided students the opportunity to collect data from adults in their community within a highly structured research project and explore a range of research questions using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…HSTA's organizational structure is community leadership, local out of school time clubs led by local teachers, implementation of personally relevant research requirements led by CRAs (Rye and Chester, 1999), multiple summer camps, and a four-year requirement for completion. This infrastructure is effective in four ways: 1) increasing educational attainment of participants (McKendall et al, 2000); 2) increasing recruitment of underserved students into the STEM workforce (Griffith, 2019;McKendall et al, 2014); 3) increasing health literacy and healthy behaviors among participants and their families (Chester et al, 2018); and 4) increasing scientists' access to under-served populations through the ability of students to partner in substantial ways with active research scientists (Siciliano et al, 2018).…”
Section: Key Strategies 4-7: the Skills Building Rsmentioning
confidence: 99%
See 2 more Smart Citations
“…HSTA's organizational structure is community leadership, local out of school time clubs led by local teachers, implementation of personally relevant research requirements led by CRAs (Rye and Chester, 1999), multiple summer camps, and a four-year requirement for completion. This infrastructure is effective in four ways: 1) increasing educational attainment of participants (McKendall et al, 2000); 2) increasing recruitment of underserved students into the STEM workforce (Griffith, 2019;McKendall et al, 2014); 3) increasing health literacy and healthy behaviors among participants and their families (Chester et al, 2018); and 4) increasing scientists' access to under-served populations through the ability of students to partner in substantial ways with active research scientists (Siciliano et al, 2018).…”
Section: Key Strategies 4-7: the Skills Building Rsmentioning
confidence: 99%
“…Although HSTA does not suffer anymore from this, dismantling this belief took a decade inside the WVU institution through successful partnerships with faculty. HSTA students have worked with researchers at the University of Pittsburgh (Bardwell et al, 2009;Branch and Chester, 2009;Branch et al, 2011;Branch et al, 2014) and Dartmouth (Siciliano et al, 2018).…”
Section: Challenges and Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature has demonstrated that community-university partnerships, service-learning, and experiential activities are critical in successful programming. Other researchers have also effectively engaged with high school students directly to address health disparities (Siciliano et al, 2018;Sprague Martinez et al, 2016). While there are curricula available for high school teachers to use to integrate health disparities content in their teaching, these curricula have not been evaluated in the peer-reviewed literature (Teaching Tolerance, 2019; University of Maryland, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to benefitting participating youth, HSTA's CBPR projects have also demonstrated improved research quality. In one project investigating knee osteoarthritis, high school students exceeded expectations of 100 surveys to collect over 1000 in hard to reach Appalachian communities (Siciliano et al, 2018). As a model, HSTA clearly documents the feasibility and potential impact of STEM pipeline programs that use CBPR to engage high school students to conduct research addressing issues in their local community.…”
mentioning
confidence: 99%